When farmers walk away: a mixed-methods investigation of farmland abandonment through land-use change and farmer interviews in the Chengdu-Chongqing economic circle, southwestern China - Wu, Qiang; Zhou, Peng; Dai, Yunchuan (Frontiers in Environmental Science, 2025)
Farmland abandonment poses a critical threat to food security, ecological stability, and sustainable rural development, particularly in China’s hilly and mountainous regions. This study examines the spatial distribution and socioeconomic determinants of farmland abandonment in the Chengdu–Chongqing Economic Circle (CCEC), located in the upper Yangtze River Basin. Drawing on multi-temporal land use data, we quantify the extent and spatial variation of abandonment over the past decade. Supplementary household survey data were analyzed using a Binary Logistic Regression Model to identify key drivers behind farmers’ abandonment decisions. The results reveal pronounced spatial heterogeneity, with dryland abandonment exceeding 20% and paddy field abandonment surpassing 8% in peripheral mountainous zones. Major positive drivers include household labor aging (β = 1.218; marginal effect: 27.1%), low net farming income (below 7500 RMB/hectare; 21.4%), high dependence on hired labor (18.3%), and land fragmentation (β = 0.217; 5.3%). In contrast, higher educational attainment, access to agricultural subsidies, greater policy awareness, and larger household size significantly reduce abandonment likelihood. While natural and institutional factors were considered, socioeconomic variables exhibited more statistically robust and consistent influence on farmland abandonment decisions within the study area. These findings provide empirical insights for designing targeted rural revitalization policies that address labor shortages, enhance agricultural returns, and promote sustainable land use in mountainous regions.